Karakteristik Pemecahan Masalah Bangun Datar Siswa SMP Bergaya Kognitif Field Independent dan Field Dependent - Muhammad Rizal; Maxinus Jaeng; Pathuddin Pathuddin (Jurnal Kreatif Online, 2022)
The purpose of this study was to describe the characteristics of geometry problem solving in junior high school with cognitive style field independent and field dependent. This study used a qualitative method based on Polya's problem solving. The results show that the characteristics of the field independent subject are focusing on the details of problem information, focusing on facts and principles that exist with the problem being asked by relating knowledge and experience that have been studied previously, applying ideas to solve problems and focusing on facts and principles with its own structure, and processing information by checking the results of the work. Characteristics of field dependent subject tend to think globally takes longer, mastering things that have been previously learned and used in new situations, forming a connection between a person's new experience and what is already stored in his mind, and processing information by rechecking the work.